Conceptual framework for sewer pump problems allowing for fuzzy logic application - Bester, A.J.; Jacobs, H.E.; Tulleken, J. (Water S. A., 2015)
Sewer pump station problems in separate sewer systems (separate from stormwater drainage systems) were investigated in order to derive a conceptual framework for decision making. Notwithstanding the fundamental service that efficient sewage pumping provides to a community, it was apparent that limited research has been published on the topic. Research was undertaken to identify, investigate and classify problems at existing operational sewage pump stations by means of site visits, interviews, and an extensive knowledge review. A conceptual framework for sewer pump problems was subsequently derived. The application of the framework is illustrated by means of a fuzzy logic approach to one of the problem classes identified. This study sets the scene for further research into fuzzy-based efficiency indices pertaining to different sewer system components and the ultimate application in sewer system decision support tools.